Medical student education in transfusion medicine: Proposal from the "European and Mediterranean initiative in transfusion medicine". Issue 5 (October 2018) - Garraud, Olivier; Brand, Anneke; Henschler, Reinhard; Vuk, Tomislav; Haddad, Antoine; Lozano, Miguel; Ertuğrul Örüç, Nigar; Politis, Constantina; de Angelis, Vincenzo; Laspina, Stefan; Tissot, Jean-Daniel; ,
Abstract: A large body of observations indicate that there is an inconsistent knowledge of Transfusion Medicine among health care professionals as well as inconsistent knowledge in all aspects of the transfusion process, from blood donation to transfusion on the ward. It is obvious to consider that appropriate education in Transfusion Medicine should be achieved in the education of specialists who will prescribe transfusion on a regular basis (hematologists, critical care specialists, anaethesiologists and others.) However, we also believe that education in Transfusion Medicine should also be delivered to almost all other medical specialists who may prescribe blood components. The variability in education of undergraduates in medical schools is universal most likely due to an absence of a predefined common platform. This paper, therefore, focuses on education at the undergraduate level and advocates coverage of the essential physiology and pathophysiology of blood as applied to blood transfusion as well as the medical and societal aspects of issues related to blood donation. It proposes incremental levels of training in Transfusion Medicine, with what is being therefore referred to as 'A', 'B', 'C' etc. curricula in ascending order of complexity; for example, 'A' and 'B' levels would involve medical, midwifery and nursing students, covering a broad base of the subject: they will be detailed in the present essay; ongoing further curricula will focus on physicians and other professionals working within the area or with responsibility for different aspects of the transfusion chain. It is intended that these courses include aspects of donor care, patient care and the appropriate use, safety and effectiveness of blood products. Next, it is advocated that curricula are addressed not only for high-income countries but also for middle- and low-income ones.